Mucin expression in normal and diseased states of the stomach : a histochemical and immunohistochemical study - Taylor, Kathryn (Division of Anatomical Pathology, 2017)
Nine human mucin genes have been described, which express glycoproteins MUCJ,2,3,4 ,5AC,5B,6, 7, and 8 in various tissues. It has been shown that different mucins are expressed in various gastric disease states as compared to the normal. In this study histochemical and immunohistochemical methods were used to determine the type of mucin and the pattern of staining in 54 patients with a variety of gastric conditions [i.e. normal controls, foetal stomachs, chronic active gastritis, low grade dysplasia, intestinal metaplasia (associated with gastritis, benign ulcers, dysplasia and cancer), early and advanced intestinal type adenocarcinoma, and diffuse adenocarcinoma]. MUCJ-7 antibodies were used in the study, this being the first study to all assess seven MUC antibodies in the various conditions. It is also the first study to assess the pattern of mucin staining in foetal stomachs. Normal controls were immunoreactive for MUC4, 5 and 6, and gastritis specimens showed similar results, although the latter showed more MUCJ immunoreactivity. Whereas early foetal stomach showed no MUC immunoreactivity, MUC4, 5 and 6 were present from the early second trimester onwards. There was no significant difference between dysplasia and intestinal metaplasia, both categories showing expression of MUC2 and 3 predominantly. Early intestinal type adenocarcinomas did not show any mucins in the majority of cases. Advanced intestinal type adenocarcinomas showed immunoreactivity predominantly for MUCJ, 5 and 6, as well as MUC2 in some cases. Diffuse adenocarcinomas showed strong positive MUC2 and MUC6 staining, and in some cases MUC5 and 7. In conclusion this study has shown different patterns of mucin immunoreactivity in various gastric disease states. Specimens with dysplasia, intestinal metaplasia, late intestinal type adenocarcinoma and diffuse gastric cancer were characterized by increased diversity of mucin gene expression, whereas early intestinal cancer showed loss of mucin immunoreactivity.